Textbook of stroke medicine - Brainin, Michael; Heiss, Wolf-Dieter; Tabernig, Susanne (Cambridge, U.K. : Cambridge University Press, 2014)
This concise and informative Textbook of Stroke Medicine is aimed at doctors preparing to specialize in stroke care and strokologists looking for concise but in-depth scientific guidance on stroke management. Its practical approach covers all important issues of prevention, diagnosis, and treatment of cerebrovascular diseases. Dedicated chapters give a thorough review of all clinical issues. Fully revised throughout, the new edition has expanded sections on topics of rising practical importance, such as diagnostic imaging, stroke unit management, monitoring and management of complications including infections, recommendations for thrombolysis, interventions and neurosurgical procedures, and clear and balanced recommendations for secondary prevention. Neuropsychological syndromes are explained and an up-to-date view on neurorehabilitation is presented. The authors are all experts in their field and many of them have been working together in a teaching faculty for the European Master in Stroke Medicine Programme, which is supported by the European Stroke Organization.
Bibliogr. odkazy
Register
Keywords: príhoda náhla cievna mozgová ischemická -- etiológia -- patofyziológia -- epidemiológia; príhoda náhla cievna mozgová ischemická -- diagnostika -- zobrazovanie diagnostické -- terapia; rehabilitácia po náhlej cievnej mozgovej príhode -- metódy; faktory rizikové; prevencia sekundárna; učebnica